Encounters between Jesuits and Protestants in Africa - Aleksander Maryks, Robert; Mkenda, Festo (Jesuit Studies, 2018)
The essays in Encounters between Jesuits and Protestants in Africa offer a critical reflection on the often more competitive than cordial relationships between Jesuit and Protestant missionaries in nineteenth- and early twentieth-century Africa. This volume is the result of the second Boston College International Symposium on Jesuit Studies held at the Jesuit Historical Institute in Africa (Nairobi, Kenya) in 2016. Thanks to generous support of the Institute for Advanced Jesuit Studies at Boston College, this volume is available in Open Access. Readership: All interested in Jesuit studies, mission history, Christianity in Africa, Catholic-Protestant encounters and ecumenism in general.